Effect of residual stresses in injection molded cyclic olefin copolymer during microfabrication : hot embossing as well as thermal bonding - Jena, Rajeeb Kumar (2013)
Microfabrication using replication techniques such as hot embossing and injection molding followed by thermal sealing with a cover plate have been widely used in the large scale manufacturing of polymer based micro-devices for bio and chemical-MEMS (Micro Electro Mechanical Systems) applications. While several parameters are known to affect the integrity of microchannel replication, they have not been characterized and studied. These parameters include the influence of (i) in built residual stresses in substrate materials, made by injection molding, on replication fidelity during microfabrication using the hot embossing technique, (ii) sealing of injection molded microchips during thermal bonding and (iii) replication fidelity of annealed and unannealed substrates during hot embossing. This is the focus of the current work. Residual stresses were analysed using a grey-field polariscope and the fidelity of microreplication was characterized using a PLμ confocal microscope and a scanning electron microscope. It was found that the significant variation in replication fidelity of the injection molded substrate correlated well with the observed differences in the distribution of residual stresses. Good replication was obtained in regions with low residual stresses. The annealed substrate which had a low residual stress state with little chain orientation exhibited no variation in replication fidelity both along and across the flow direction of the injection molded substrate. Furthermore, the microchannels in the unannealed injection molding substrate exhibited significant distortion and deformation during subsequent thermal bonding.